Plasmid-mediated tigecycline-resistant gene tet(X4) in Escherichia coli from food-producing animals, China, 2008–2018 - Chengtao Sun; Mingquan Cui; Shan Zhang; Hejia Wang; Li Song; Chunping Zhang; Qi Zhao; Dejun Liu; Yang Wang; Jianzhong Shen; Shixin Xu; Congming Wu (Emerging Microbes and Infections)
The recent emergence of plasmid-mediated tigecycline resistance genes, tet(X3) and tet(X4), in animals and humans in China would pose a foreseeable threat to public health. To illustrate this paradigm shift in tigecycline resistance, here, covering the period 2008-2018, we retrospectively analysed a national strain collection of Escherichia coli (n = 2254), obtained from chickens and pigs, in six representative provinces of China. The gene tet(X4) was identified in five pig isolates collected in 2016 and 2018 from the provinces of Sichuan (3/15, 2018), Henan (1/25, 2018) and Guangdong (1/28, 2016), but not in the isolates prior to 2016. None of the isolates was detected harbouring tet(X3). All tet(X4)-positive E. coli exhibited high levels of tigecycline resistance (MICs, 16-64 mg/L), and two were confirmed as colistin resistant, harbouring chromosome-borne mcr-1 gene. The gene tet(X4) was detected on a plasmid in all five isolates, whereas a co-location of tet(X4) on the chromosome of one isolate was observed. Diverse host strains and novel plasmids related to the tet(X4) gene were observed. Our timely findings of the recent emergence of tet(X4) gene in food animal support the rapid surveillance and eradication of this gene before it is established.